Population-based patterns of care in the first-line treatment of patients with advanced esophagogastric adenocarcinoma in Germany - Hofheinz, Ralf-Dieter; Batran, Salah-Eddin al-; Ridwelski, Karsten; Görg, Christian; Wehle, Klaus; Birth, Matthias; Fetscher, Sebastian; Scheiber, Harald; Lukan, Nadine; Lordick, Florian (Onkologie, 2010)
Background: Randomized studies proved the efficacy of new drugs for the systemic treatment of advanced gastric cancer in the past 5 years. However, little is known about the use of firstline chemotherapy in clinical practice in patients with advanced or metastatic adenocarcinoma of the esophagogastric junction (AEG) and the stomach. We investigated temporal trends in therapy and factors influencing treatment decisions for these patients during a 4-year period. Patients and Methods: 1058 patients (median age 67 years) with advanced AEG or gastric cancers undergoing treatment decisions were documented with the Therapiemonitor® in 2006-2009. Therapiemonitor collects population-based data regarding treatment decisions and strategies. Time trends of drug use and intensity in the first-line treatment were analyzed in the entire patient group and according to age (cut-off 65 years) and Karnofsky performance status (KPS; cut-off 80%). Results: Over time, the use of oxaliplatin and docetaxel as well as capecitabine increased while cisplatin and irinotecan use slightly declined. The use of chemotherapy triplets rose from 10.1% in 2006 to 47.0% in 2009. Treatment patterns significantly varied by age and KPS: Older patients were significantly less likely to receive chemotherapy triplets, cisplatin and docetaxel but tended to more often receive oxaliplatin. Likewise, triplets, cisplatin and docetaxel were less frequently used in patients with KPS < 80%, while capecitabine and irinotecan were significantly more often used in this patient group. Conclusions: A clear tendency towards the use of more intensive chemotherapy regimens in patients with AEG and gastric cancer was observed over time. Older or less fit patients were treated preferably with monotherapy or chemotherapy doublets during 2006-2009. Oxaliplatin and docetaxel use has substantially risen.
Gesehen am 14.03.2023
Published online: September 20, 2010